2011
DOI: 10.1111/j.1748-1716.2011.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute hypobaric hypoxia on blood flow distribution in brain

Abstract: These findings underscore the specific sensitivity of the frontal lobe to acute hypobaric hypoxia and of limbic and central structures to blood gas changes emphasizing the involvement of these brain areas in acute hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
1
31
1
Order By: Relevance
“…PAGANI et al [29] showed that the changes in regional cerebral blood flow (rCBF) in response to hypoxia are different in the gray and white matter. They found a greater degree of rCBF in the forebrain grey matter during acute hypoxia and speculated that this localised response might be ascribed to an acute compensatory mechanism involving regions with increased sensitivity to oxygen deficits, possibly because they would develop reversible neuronal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…PAGANI et al [29] showed that the changes in regional cerebral blood flow (rCBF) in response to hypoxia are different in the gray and white matter. They found a greater degree of rCBF in the forebrain grey matter during acute hypoxia and speculated that this localised response might be ascribed to an acute compensatory mechanism involving regions with increased sensitivity to oxygen deficits, possibly because they would develop reversible neuronal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of blood flow to the head and brain is not uniform during exercise [62], [63]. Cerebral blood flow is heterogeneously distributed under hypoxia [64], [65]. Moreover, dynamic cerebral autoregulation may be impaired at rest [66] and during exercise [67] under moderate hypoxia, although hypocapnia is thought to counteract impaired dynamic cerebral autoregulation under hypoxia [68].…”
Section: Discussionmentioning
confidence: 99%
“…During mild to moderate inspiratory hypoxia, cerebral blood flow increases to compensate for the reduced blood oxygenation, maintaining cerebral oxygen delivery and metabolic function (19). There has been some evidence of regional differences in the CBF response to hypoxia (20–22) which may indicate there are also different lactate responses regionally. Similarly, grey matter is considered more metabolically active and has greater CBF compared to white matter (19).…”
Section: Discussionmentioning
confidence: 99%